COMBINATION OF HIBISCUS SABDARIFFA LINN, FLOWER AND WHITE GINGER TEA ON BLOOD PRESSURE REDUCTION IN THE ELDERLY - Putri, Farisa Adinda; Hidayati, Nur; Maghfuroh, Lilis (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Hypertension is a common health problem among the elderly. This study aims to determine the effectiveness of Hibiscus sabdariffa Linn. flower and white ginger tea in reducing blood pressure in the elderly. This quasi-experimental study employed a control group design. The study was conducted on 64 elderly and distributed equally to intervention and control group. The intervention group received Hibiscus sabdariffa Linn. flower and white ginger tea, while the control group administered antihypertensive medication. Blood pressure was measured using a digital sphygmomanometer. Data were analyzed using a t-test (α ≤ 0.05). In the intervention group, the mean systolic blood pressure decreased 11.7 and the mean diastolic blood pressure also dropped 7.8. In the control group, the mean systolic blood pressure reduced 12.5; and a decrease in mean diastolic blood pressure of 7.76. A notable change was detected between pre-test and post-test measurements in both the intervention and control groups (p = 0.000; p = 0.000). However, post-test systolic and diastolic blood pressure remained comparable between the two groups, showing no significant difference (p = 0.441; p = 0.856). Hibiscus sabdariffa Linn. flower and white ginger tea have demonstrated efficacy in reducing blood pressure in the elderly, comparable to antihypertensive drugs.